2011
DOI: 10.1159/000334065
|View full text |Cite
|
Sign up to set email alerts
|

From Karyotyping to Array-CGH in Prenatal Diagnosis

Abstract: Conventional karyotyping detects chromosomal anomalies in up to 35% of pregnancies with fetal ultrasound anomalies, depending on the number and type of these anomalies. Extensive experience gained in the past decades has shown that prenatal karyotyping is a robust technique which can detect the majority of germline chromosomal anomalies. For most of these anomalies the phenotype is known. In postnatal diagnosis of patients with congenital anomalies and intellectual disability, array-CGH/SNP array has become th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 168 publications
0
41
0
3
Order By: Relevance
“…The value of whole genomic analysis is the ability to identify new genetic deletion or duplication syndromes [14]. Identifying new associations is not possible with the utilization of an array designed to detect known genetic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The value of whole genomic analysis is the ability to identify new genetic deletion or duplication syndromes [14]. Identifying new associations is not possible with the utilization of an array designed to detect known genetic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive prenatal diagnosis (NIPD), based on cell-free fetal DNA in maternal serum, enables the detection of a selected set of diagnoses (i.e., common aneuploidies) with a high sensitivity and without risk for miscarriages Papageorgiou et al, 2011]. Thus, in the near future, it is imaginable that NIPD will replace all the current biochemical screening tests or be the first-tier test after biochemical screening indicates an increased risk for Down syndrome, while genome-wide array investigations will be used only for those cases with abnormal ultrasound results [Lichtenbelt et al, 2011].…”
Section: Arrays In the Prenatal Setting: For What Indication?mentioning
confidence: 99%
“…As prior studies indicated, conventional karyotyping only identify chromosomal anomalies in about 35% of pregnancies with fetal ultrasound abnormalities, depending on the types of these anomalies [3]. Molecular cytogenetic techniques such as fluorescent in situ hybridisation (FISH), quantitative fluorescent PCR (QF-PCR) and multiplex ligation-dependent probe amplification (MLPA) overcome some of those limitations and are used as adjuncts to conventional methods for detecting common chromosome numerical anomalies [1], but none of them provides a genome wide screening for unexpected imbalances [4].…”
Section: Introductionmentioning
confidence: 99%